Disentangling the importance of space and host tree for the beta-diversity of beetles, fungi, and bacteria: Lessons from a large dead-wood experiment. (April 2022) - Rieker, Daniel; Krah, Franz-S.; Gossner, Martin M.; Uhl, Britta; Ambarli, Didem; Baber, Kristin; Buscot, François; Hofrichter, Martin; Hoppe, Björn; Kahl, Tiemo; Kellner, Harald; Moll, Julia; et al.
Abstract: Forestry in Europe changed the tree species composition and reduced dead-wood amount and heterogeneity, and therefore negatively affected saproxylic diversity. Efficient conservation requires knowledge about the importance of the relevant diversity drivers across taxa. We examined the relative importance of space vs. host for saproxylic diversity at a spatial extend of 600 km in Germany. Further, we disentangled effects of among regions, forest stands, host clades, and tree species on saproxylic diversity. This allows inferences for spatial- and host tree-related conservation strategies. Beetle, fungal sporocarp, molecular-derived fungal, and bacterial communities were studied in a large nested dead-wood experiment comprising 11 tree species. We used multiplicative diversity partitioning to assess the diversity of rare, typical, and dominant species. The beta-diversity of beetles and fungal sporocarps was equally explained by space and host, but that of molecular fungi and bacteria mainly by the host. Across taxa, beta-diversity was higher among forest stands than among regions. However, for beetles and fungal sporocarps, differences among regions were also important. Host tree clade and host tree species were important for beetle and host clade for fungal sporocarp beta-diversity. Host tree species was more important than host clade for the beta-diversity of molecular fungi and bacteria. The divergent response of different taxa to space and host calls into question the use of a simple spatially-centered or host-centered strategy. Instead, a high dead-wood tree species diversity on a broad spatial coverage at the national scale in temperate European forests is necessary to maintain rare and abundant species. Highlights: Relative importance of space versus host across saproxylic taxa is unknown. Beetle diversity is driven by space and host, microbial diversity mainly by the host. Different fungal diversity measures yielded different results. Conservation requires dead-wood enrichment with different clades and tree species. Dead-wood enrichment must be established in different forest types across regions.